2017
DOI: 10.1530/rep-16-0627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that follicle development is accelerated in vitro compared to in vivo

Abstract: In this study, we systematically compared the morphological, functional and molecular characteristics of granulosa cells and oocytes obtained by a three-dimensional model of ovine ovarian follicular growth with those of follicles recovered Preantral follicles of 200 µm diameter were recovered and cultured up to 950 µm over a 20-day period. Compared with follicles, the culture conditions maintained follicle survival, with no difference in the rate of atresia. However, the conditions induced a slight decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
6
21
0
Order By: Relevance
“…In the case of ovarian follicles, it is responsible for the transition from preantral to antral follicle [25]. The Cadoret et al study showed a decreased KIT expression in in vitro culture of ovarian follicle cells, which was explained by the reduced oocyte growth rate in vitro relative to in vivo [26]. In the case of our studies, we showed a decrease in the expression of the KIT gene after IVM which confirms its role of the proliferation and differentiation of oocytes.…”
Section: Discussionsupporting
confidence: 80%
“…In the case of ovarian follicles, it is responsible for the transition from preantral to antral follicle [25]. The Cadoret et al study showed a decreased KIT expression in in vitro culture of ovarian follicle cells, which was explained by the reduced oocyte growth rate in vitro relative to in vivo [26]. In the case of our studies, we showed a decrease in the expression of the KIT gene after IVM which confirms its role of the proliferation and differentiation of oocytes.…”
Section: Discussionsupporting
confidence: 80%
“…This redundancy in pathways might explain the moderate impact of 4HC on their expression levels. As folliculogenesis is accelerated in vitro in several species [55], slowing down the activation events by acting on the PI3K pathway appears to be an interesting approach to improving culture yields. Furthermore, it has been reported in mice that mTORC1 inhibition using Everolimus (EVE) prevents follicular activation and protects the ovarian reserve against chemotherapeutic treatment [53].…”
Section: Discussionmentioning
confidence: 99%
“…In Icelandic sheep, the gene NCOA1 can alter the expression of multiple key genes PBP, AIB3 , and FGFR2 , which are important for aberrant labyrinth morphogenesis of the placenta and embryonic lethality ( Chen et al, 2010 ; Huang et al, 2011 ). In Finnsheep, the five candidate genes INHBB, NF1, FLT1, PTGS2 , and PLCB3 played important roles in the development of folliculogenesis and LH signaling ( Ding et al, 2006 ; Tal et al, 2014 ; De Cesaro et al, 2015 ; Ben Sassi et al, 2016 ; Cadoret et al, 2017 ). For example, the INHBB gene encodes an inhibitor of apoptosis, which regulates porcine ovarian follicular atresia ( Terenina et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%